THE QUANTITATIVE EVIDENCE OF MALARIAL TRANSMISSION AND ITS ASSOCIATES IN BAHAWALPUR, PAKISTAN - Zaidi, Syed Arif Ahmed; Kokab, Farkhanda; Bukhari, Ijaz Ahmad; Nasir, Jamal Abdul (Journal of Ayub Medical College Abbottabad, 2015)
Background: Malaria transmission is an extremely complex condition that is manifested differently in different parts of the world. In Pakistan, malaria is still endemic in many areas. Plasmodium vivax and Plasmodium falciparum are identified to be the most prevalent species of malaria in Pakistan. A great deal of work regarding malarial transmission is available at regional level in Pakistan but the evidence of malaria with its associates in Bahawalpur is scarce. The present study was planned to see the pattern of malarial transmission in the city of Bahawalpur, Pakistan. Methods: In this cross-sectional study data on 1623 subjects was collected. Giemsa stain thick and thin blood films were used as diagnostic tools for malarial transmission. Bivariate statistical analysis in addition was employed to identify the associates of malarial prevalence. Results: Out of 1623 subjects screened, 70 (4.3%) were found infected. Plasmodium vivax was seen in the majority 61 (77.2 %). Plasmodium falciparum was the second common species identified in 16 (22.8%) cases. As expected place of residence, window screening, malarial knowledge and behaviours of sleeping were seen to be significant associates of malarial transmission in Bahawalpur. Conclusion: The findings revealed that Bahawalpur falls in the category of low to moderate level malarial transmission as compared to other regions of Pakistan. Plasmodium vivax was the commonest type of malaria diagnosed in Bahawalpur. Geographic location, house safety, malarial knowledge, and behaviour of sleeping are the highly significant associates of malarial transmission in Bahawalpur. Keywords: Bivariate analysis; Malaria; Plasmodium